Anti-imperialist independence: Lyndon B. Johnson in Costa Rica and the Vietnam solidarity of the student movement in 1968 - Chaves Zamora, Randall Andrés (2021)
In 1968, a group of students at the University of Costa Rica (UCR) skillfully combined concepts of globalization with nationalism. The student movement utilized solidarity with Vietnam, the celebration of independence and sovereignty to oppose the visit of the president of the United States to Costa Rica. This article proposes that solidarity, anti-imperialism and new ways of interpreting the Costa Rican past were substantial changes in the political culture of the youth during that event, which turned into one of most relevant moments of the Cold War for the Costa Rican student movement. The article develops this argument in four sections: the first part explains the visit of the US president to the country, while the second part analyzes the considerable student opposition it generated. The third section reviews the way in which the youth confronted the repercussions of their protest. Lastly, the article examines the immediate trajectory of the students’ political vocabulary, pointing out the case of Vietnam Solidarity, their assessments of the Latin American context and the emerging student anti-imperialism.